Influence of Wrinkle Structure on Properties of Na-doped ZnO Films - Trinh, Bui Nguyen Quoc; Nhat Minh, Pham (VNU Journal of Science: Mathematics - Physics; Vol 40 No 3DO - 10.25073/2588-1124/vnumap.4937, 2024)
Un-doped ZnO and Na-doped ZnO (NZO) thin films with various Na doping concentrations were successfully fabricated on glass substrates by a sol-gel process. The effect of Na ions at concentrations of 0, 1, 2, 3, 4, and 5% on the crystalline structure, surface morphology, and optoelectronic properties of ZnO films was studied using appropriate measurement techniques. XRD analysis revealed a polycrystalline hexagonal wurtzite structure in the NZO films. The NZO films' average crystal size ranged from 17.7 nm to 19.6 nm. SEM micrographs showed that wrinkle network appeared in the pure and doped ZnO films due to solvent evaporation during the thermal annealing process. UV-Vis spectroscopy pointed out that the average transmittance of NZO films is as large as ca. 78%. The optical bandgap of the films varied slightly between 3.235 eV for the pure ZnO and 3.246 eV for the Na 5% doped NZO film. When Na ions were doped into the NZO films, the electrical conductivity improved. Moreover, the absorption figure of merit exhibited the largest value of 0.981 Ω -1 cm -1 for the fabricated NZO films, which enables the use of these films for solar cells and for other optoelectronic applications.